If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 1) + -1(x + 2) + (x + 3) = 0 Reorder the terms: x + (1 + x) + -1(x + 2) + (x + 3) = 0 Remove parenthesis around (1 + x) x + 1 + x + -1(x + 2) + (x + 3) = 0 Reorder the terms: x + 1 + x + -1(2 + x) + (x + 3) = 0 x + 1 + x + (2 * -1 + x * -1) + (x + 3) = 0 x + 1 + x + (-2 + -1x) + (x + 3) = 0 Reorder the terms: x + 1 + x + -2 + -1x + (3 + x) = 0 Remove parenthesis around (3 + x) x + 1 + x + -2 + -1x + 3 + x = 0 Reorder the terms: 1 + -2 + 3 + x + x + -1x + x = 0 Combine like terms: 1 + -2 = -1 -1 + 3 + x + x + -1x + x = 0 Combine like terms: -1 + 3 = 2 2 + x + x + -1x + x = 0 Combine like terms: x + x = 2x 2 + 2x + -1x + x = 0 Combine like terms: 2x + -1x = 1x 2 + 1x + x = 0 Combine like terms: 1x + x = 2x 2 + 2x = 0 Solving 2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 0=v^2-10v+24 | | 6(x-4)=-3(x-4) | | A/9=123 | | f=-2+4x-1+-1x | | 6z^2=-19z-10 | | H--184/22=30 | | x^2+y^2+16x+12y=0 | | 22/h--184=30 | | S/3=4 | | 0=v^2+12v+27 | | 9s^2-9s=0 | | 6.7=t/4.9 | | 666=91+23c | | X/4-3x/2=-28.4 | | Q+9=7 | | Y=-5x^2+2x+11 | | 6.7m=t/4.9 | | 24(q+445)=-528 | | 2a-4=5b | | 0=w^2+9w+18 | | 21(h-944)=672 | | (U-8)*7=35 | | h+-16=-13 | | 3(y-13)=6y+24 | | r/4.4=2.8 | | 125-3n=83 | | r^2+r=72 | | f(x)=4-x^2-2x | | 35b-333=751 | | 3(y-13)=6y+12 | | 12x+10y=120 | | (E+2)*4=16 |